A Class Apart - Lewis, Susan (London Arrow Books, 2009)
Four successful female friends, each with her own secret, must keep them hidden, or risk destroying the life they have carefully built
Keywords: Mexican Americans--Civil rights -- Race relations -- Trials (Murder)